A sodium ion battery and its biomass hard carbon negative electrode material and preparation method

By pre-treating biomass to form a hard carbon electrode with plasma coating and carbonization, the method addresses gas production issues in sodium-ion batteries, enhancing electrochemical performance and extending battery life.

CN116675217BActive Publication Date: 2024-12-24HUNAN NINGNA TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310916480.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-25
Publication Date
2024-12-24
Estimated Expiration
2043-07-25

AI Technical Summary

Technical Problem

Hard carbon materials used in sodium-ion batteries are prone to adsorb water molecules, causing gas production and electrode reactions with the electrolyte, which limits their large-scale application due to defects and oxygen-containing functional groups on their surfaces.

Method used

A method involving biomass as a raw material, pre-carbonization, plasma coating treatment, and high-temperature carbonization to repair surface defects and cover active oxygen-containing groups with carbon deposition, enhancing sodium ion embedding and extraction efficiency.

Benefits of technology

The method results in a biomass hard carbon negative electrode material with improved electrochemical performance, reducing gas production and extending battery life, with a first-cycle coulomb efficiency of 92.30% and minimal gas production after 100 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116675217B_ABST
    Figure CN116675217B_ABST
Patent Text Reader

Abstract

The present invention provides a sodium ion battery and its biomass hard carbon negative electrode material and preparation method, which relate to the field of sodium ion battery electrode material preparation. The method uses biomass as raw material, dries the biomass raw material, crushes it and places it in a high-temperature tubular furnace for pre-carbonization, and places the material after pre-carbonization in a plasma chemical vapor deposition chamber for plasma coating treatment. After the coating is completed, the material is placed in a high-temperature tubular furnace for high-temperature carbonization to obtain the final biomass hard carbon; wherein, while repairing the excessive defects on the surface of the carbon material during the plasma treatment process, the active oxygen-containing groups are covered by carbon deposition coating, which effectively solves the problems of low embedding and extraction efficiency of hard carbon materials for sodium ions and short battery life caused by gas production in the later stage of hard carbon materials. In addition, the preparation process of a sodium ion battery and its biomass hard carbon negative electrode material of the present invention is simple, low cost, and the treatment process is environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of preparation of sodium ion battery electrode materials, and in particular to a sodium ion battery and a biomass hard carbon negative electrode material and a preparation method thereof. Background Art

[0002] In recent years, with the large-scale application of renewable energy, low-cost sodium-ion batteries are expected to develop rapidly in many fields such as large-scale energy storage devices, communication base stations and low-speed electric vehicles. As the most commercially promising negative electrode material, hard carbon materials have the advantages of low voltage platform, high capacity, good cycle performance and abundant sources, and have attracted great attention from researchers and the industry.

[0003] Among the many raw materials for preparing hard carbon materials, biomass raw materials are especially advantageous because of their wide sources, sustainable regeneration, low pollution and low price. Using them as raw materials to prepare hard carbon materials can not only save costs, but also alleviate the environmental pollution caused by the burning of large amounts of waste. Secondly, special texture structures and texture features will be formed during the re-growth of biomass. The original microstructure can still be maintained after carbonization, and a rich closed-pore structure will be formed during the heat treatment process. It has excellent sodium storage performance and is expected to become the most promising new low-cost, high-performance sodium-ion battery negative electrode material.

[0004] However, since hard carbon materials contain a large number of defects and oxygen-containing functional groups on their surfaces, they are prone to adsorb water molecules when smeared and exposed to the air, causing the electrode to react with the electrolyte during the charge and discharge process, resulting in a series of problems such as gas production, which restricts the large-scale application of hard carbon materials. Therefore, the development of hard carbon materials with high sodium storage performance and low gas production based on biomass carbon sources is of great significance to the industrialization of sodium-ion batteries. Summary of the invention

[0005] The present invention provides a sodium ion battery and a biomass hard carbon negative electrode material and a preparation method thereof, the purpose of which is to solve the above-mentioned problems existing in the background technology.

[0006] In order to achieve the above-mentioned purpose, the embodiment of the present invention provides a sodium ion battery and its biomass hard carbon negative electrode material and preparation method, which uses biomass as raw material, dries the biomass raw material, crushes it and places it in a high-temperature tube furnace for pre-carbonization, and places the material after pre-carbonization in a plasma chemical vapor deposition chamber for plasma coating treatment, and then places the coated material in a high-temperature tube furnace for high-temperature carbonization to obtain the final biomass hard carbon; wherein, while repairing the excessive defects on the surface of the carbon material during the plasma treatment process, the active oxygen-containing groups are covered by carbon deposition coating, which effectively solves the problems of low embedding and extraction efficiency of hard carbon materials for sodium ions and short battery life caused by gas production in the later stage of hard carbon materials. The method has simple process, low cost and environmentally friendly process.

[0007] One aspect of the present invention provides a method for preparing a biomass hard carbon negative electrode material for a sodium ion battery, comprising the following steps:

[0008] S1: Pretreatment: drying the biomass raw materials;

[0009] S2: Pre-carbonization: pre-carbonizing the pretreated biomass;

[0010] S3: plasma treatment: subjecting the pre-carbonized biomass to plasma coating treatment;

[0011] S4: high temperature carbonization: high temperature carbonization of the biomass after plasma treatment to obtain a biomass hard carbon negative electrode material for a sodium ion battery;

[0012] Among them, the pre-carbonization temperature is 200~800 ℃, and the pre-carbonization time is 2~3 h; the pre-carbonization is carried out in a tubular furnace, and an inert gas is used as a protective gas.

[0013] The plasma treatment temperature is 150~400 ℃, the input power is 100~300 W, the gas input is 5~15 mL / s, and the holding time is 10~45 min. It should be noted that if the plasma input power is too low, the hydrocarbons may not be fully ionized, affecting the surface coating of the hard carbon material and ultimately affecting the performance of the material. The plasma treatment time should not be too long. If the plasma treatment time is too long or the flow rate is too high, the hard carbon surface coating will be too thick, which will affect the specific capacity or first storage performance of the hard carbon material.

[0014] The high-temperature carbonization temperature is 1000~1700 ℃, and the high-temperature carbonization time is 2~5 h; the high-temperature carbonization is carried out in a tubular furnace, and an inert gas is used as a protective gas.

[0015] During the plasma treatment, hydrocarbon and / or inert gas atmosphere is introduced. If the hydrocarbon used is a volatile liquid, it is introduced into the plasma vapor deposition chamber by introducing inert gas.

[0016] After pre-carbonization, plasma treatment and high-temperature carbonization, the samples were cooled to room temperature in the furnace.

[0017] The inert gas is at least one of N2 and Ar.

[0018] Preferably, the drying temperature is 70-80°C and the drying time is 2-3 hours. The mixture is placed in a forced air oven to dry and remove moisture.

[0019] Preferably, the pre-carbonization heating rate is 2-5 °C / min.

[0020] Preferably, the plasma treatment heating rate is 2-5 °C / min.

[0021] Preferably, the biomass raw material is an organism naturally synthesized using the atmosphere, water and soil.

[0022] Preferably, the biomass raw material is at least one of starch, bamboo, wood, peanut shells and wheat husks.

[0023] Preferably, the hydrocarbon is an alkane, a cycloalkane or an aromatic hydrocarbon.

[0024] Preferably, the alkane is methane; the cycloalkane is cyclohexane; and the aromatic hydrocarbon is toluene.

[0025] Another aspect of the present invention provides a sodium ion battery biomass hard carbon negative electrode material obtained by the above-mentioned preparation method.

[0026] Another aspect of the present invention provides a sodium ion battery, comprising the above-mentioned sodium ion battery biomass hard carbon negative electrode material. Based on the physicochemical properties of the sodium ion battery biomass hard carbon negative electrode material obtained by the above-mentioned preparation method of the present invention, the negative electrode of the assembled sodium ion battery has excellent electrochemical properties, which well solves a series of problems such as gas production caused by the reaction of the sodium ion battery electrode with the electrolyte during the charging and discharging process. Its first-cycle coulomb efficiency is 92.30%, and the first-cycle charging specific capacity is 317.87 mAh·g -1 , and the gas production of the battery after 100 cycles is only 2.5 mL.

[0027] Reaction mechanism: The atmosphere introduced or the non-gaseous chemical substances added during the plasma treatment process of the present invention are the key raw materials for realizing the modification of hard carbon materials. The gas or non-gaseous chemical substances form active plasma under the excitation of the alternating electric field. The biomass raw materials complete atomic doping and repair of excessive surface defects under the dual effects of the active plasma physical bombardment and chemical reaction, which is beneficial to the embedding and removal of sodium ions, and can cover the oxygen-containing functional groups exposed on the surface under the action of carbon deposition coating, effectively avoiding the gas production problem of the biomass hard carbon negative electrode material during subsequent use, thereby greatly improving the electrochemical performance.

[0028] The above scheme of the present invention has the following beneficial effects:

[0029] (1) The present invention uses biomass as raw material, and during the plasma treatment process, completes the repair of excessive defects on the surface of the hard carbon material. While ensuring a high closed porosity of the material and a suitable interlayer spacing, it greatly avoids the gas production of the biomass hard carbon material during later use, and effectively solves the problem of excessive defects on the surface of the hard carbon material and the oxygen-containing functional groups that easily absorb water, which causes the biomass hard carbon material to produce gas, thereby resulting in a shorter battery life.

[0030] (2) The present invention uses biomass as a carbon source, firstly dries it, and then places the dried biomass in a tubular furnace for pre-carbonization treatment. The hard carbon material obtained after the pre-carbonization is placed in a plasma chemical vapor deposition chamber for plasma treatment. During the plasma treatment, a single or mixed atmosphere is introduced, and the hard carbon material after the plasma treatment is placed in a tubular furnace for high-temperature carbonization treatment to obtain the final product. The method has a simple process, low cost, and an environmentally friendly treatment process.

[0031] (3) The atmosphere introduced into the plasma treatment process of the present invention or the non-gaseous chemical substances added form active plasma under the stimulation of the alternating electric field. Under the dual effects of the physical bombardment of the active plasma and the chemical reaction, the biomass raw materials complete the carbon deposition on the surface of the carbon microspheres. The deposited carbon can repair the excessive defects on the surface of the hard carbon material, which can effectively avoid the gas production problem of the hard carbon material during subsequent use, thereby greatly extending the service life of the battery.

[0032] (4) Based on the synergistic effect between the various steps, the present invention can repair excessive defects on the surface of the hard carbon material through carbon deposition coating, cover up the active oxygen-containing groups, and reduce the gas production problem of the biomass hard carbon negative electrode material during the later use process, while ensuring that the skeleton structure of the biomass raw material remains unchanged. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 is a schematic diagram of a plasma treatment process according to an embodiment of the present invention;

[0035] Figure 2 is the first cycle charge and discharge curve of the sodium ion battery of Example 1 of the present invention;

[0036] Figure 3 is the first cycle charge and discharge curve of the sodium ion battery of Example 6 of the present invention;

[0037] Figure 4 is the first cycle charge and discharge curve of the sodium ion battery of Example 8 of the present invention;

[0038] Figure 5 This is the first cycle charge and discharge curve of the sodium ion battery of Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0039] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0040] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0041] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0042] In view of the existing problems, the present invention provides a sodium ion battery and a biomass hard carbon negative electrode material and a preparation method thereof.

[0043] like Figure 1 As shown, an embodiment of the present invention provides a schematic diagram of a plasma treatment process for a method for preparing a biomass hard carbon negative electrode material for a sodium ion battery.

[0044] Example 1

[0045] A method for preparing a biomass hard carbon negative electrode material for a sodium ion battery comprises the following steps:

[0046] Step 1: Drying: 5 g of bamboo powder was placed in a forced air drying oven at 80 °C for 2 h to remove moisture;

[0047] Step 2: Pre-carbonization: the precursor obtained after step 1 is placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min under an argon atmosphere, pre-carbonized for 3 hours, cooled to room temperature, taken out, and ground;

[0048] Step 3: Plasma treatment: the material obtained after step 2 is placed in a plasma vapor deposition chamber, CH4 is introduced at a gas input flow rate of 10 mL / s, the plasma input power is 200 W, and the temperature is increased to 200°C at a rate of 5°C / min, and the temperature is kept for 20 min. After the heat preservation is completed, the sample is cooled to room temperature with the furnace to obtain a plasma-treated sample;

[0049] Step 4: High-temperature carbonization: the plasma-treated sample obtained after step 3 was placed in a tube furnace and heated to 1300 °C at 2 °C / min for 3 h. The sample was then cooled to room temperature and ground to obtain a bamboo powder pyrolysis hard carbon material.

[0050] Step 5: Assemble the biomass hard carbon negative electrode material prepared above into a sodium ion battery.

[0051] According to the mass ratio of 92%:3%:1.5%:3.5%, 184 mg of bamboo powder pyrolysis hard carbon electrode material powder, 6 mg of conductive carbon black, 6 mg of 2% (w / w) carboxymethyl cellulose solution, and 17.5 mg of 40% (w / w) styrene-butadiene rubber were weighed, and an appropriate amount of deionized water was added dropwise. The mixture was stirred for 20 min until it became a uniform slurry. A 100 μm scraper was used to evenly coat the slurry on the surface of the copper (Cu) foil, and the slurry was dried in a forced air drying oven at 105 °C for 2 h. The Cu foil with active material was cut into disc-shaped negative electrode sheets, which were then transferred to a glove box for standby use.

[0052] The assembly of the simulated battery was carried out in a MIKROUNA glove box filled with Ar atmosphere, using the prepared carbon material electrode as the negative electrode, commercial electrolyte 1.0 mol / L NaPF6 / EC:DMC (1:1) (V:V) as the electrolyte, and Na metal sheet as the counter electrode to assemble a 2016 button cell.

[0053] The first cycle charge and discharge curve of the sodium ion battery is as follows Figure 2 shown.

[0054] Step 6: Assemble the biomass hard carbon negative electrode material prepared above into a sodium ion battery and measure the gas production during the cycle.

[0055] The measurement of battery gas production requires assembly into a soft-pack battery first. Commercial nickel-iron-manganese layered oxide is used for the positive electrode, and the prepared hard carbon is used for the negative electrode. The negative electrode is slurried, coated, dried, die-cut, stacked, injected, and soft-pack packaged in a mass ratio of 92%:3%:1.5%:3.5% to assemble into a single soft-pack battery with a capacity of 1 Ah. The volume measurement of soft-pack batteries is mainly based on the Archimedean principle. The soft-pack battery is hung on a universal testing machine, the reading is recorded, and then the battery is slowly and completely immersed in non-conductive vacuum pump oil (density 0.8595 cm -3 ), record the reading of the tensile instrument again after the instrument stabilizes, which is the volume of the soft-pack battery, and the volume difference before and after the cycle is the gas production.

[0056] Example 2

[0057] A method for preparing a biomass hard carbon negative electrode material for a sodium ion battery comprises the following steps:

[0058] Step 1: Drying: 5 g of bamboo powder was placed in a forced air drying oven at 80 °C for 2 h to remove moisture;

[0059] Step 2: Pre-carbonization: the precursor obtained after step 1 is placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min under an argon atmosphere, pre-carbonized for 3 hours, cooled to room temperature, taken out, and ground;

[0060] Step 3: Plasma treatment: the material obtained after step 2 is placed in a plasma vapor deposition chamber, CH4 is introduced at a gas input flow rate of 10 mL / s, the plasma input power is 200 W, and the temperature is increased to 100°C at a rate of 5°C / min, and the temperature is kept for 20 min. After the heat preservation is completed, the sample is cooled to room temperature with the furnace to obtain a plasma-treated sample;

[0061] Step 4: High-temperature carbonization: the plasma-treated sample obtained after step 3 was placed in a tube furnace and heated to 1300 °C at 2 °C / min for 3 h. The sample was then cooled to room temperature and ground to obtain a bamboo powder pyrolysis hard carbon material.

[0062] Step 5: using the carbon material prepared above as an active material of a negative electrode material of a battery for preparing a sodium ion battery, the specific method is the same as that of Example 1;

[0063] Step 6: The material prepared above is used as the active material of the battery negative electrode material for measuring the gas production during the post-recycling process of the sodium ion battery. The specific method is the same as that in Example 1.

[0064] Example 3

[0065] A method for preparing a biomass hard carbon negative electrode material for a sodium ion battery comprises the following steps:

[0066] Step 1: Drying: 5 g of bamboo powder was placed in a forced air drying oven at 80 °C for 2 h to remove moisture;

[0067] Step 2: Pre-carbonization: the precursor obtained after step 1 is placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min under an argon atmosphere, pre-carbonized for 3 hours, cooled to room temperature, taken out, and ground;

[0068] Step 3: Plasma treatment: the material obtained after step 2 is placed in a plasma vapor deposition chamber, CH4 is introduced at a gas input flow rate of 10 mL / s, the plasma input power is 100 W, and the temperature is increased to 200°C at a rate of 5°C / min, and the temperature is kept for 20 min. After the heat preservation is completed, the sample is cooled to room temperature with the furnace to obtain a plasma-treated sample;

[0069] Step 4: High-temperature carbonization: the plasma-treated sample obtained after step 3 was placed in a tube furnace and heated to 1300 °C at 2 °C / min for 3 h. The sample was then cooled to room temperature and ground to obtain a bamboo powder pyrolysis hard carbon material.

[0070] Step 5: using the carbon material prepared above as an active material of a negative electrode material of a battery for preparing a sodium ion battery, the specific method is the same as that of Example 1;

[0071] Step 6: The material prepared above is used as the active material of the battery negative electrode material for measuring the gas production during the post-recycling process of the sodium ion battery. The specific method is the same as that in Example 1.

[0072] Example 4

[0073] A method for preparing a biomass hard carbon negative electrode material for a sodium ion battery comprises the following steps:

[0074] Step 1: Drying: 5 g of bamboo powder was placed in a forced air drying oven at 80 °C for 2 h to remove moisture;

[0075] Step 2: Pre-carbonization: the precursor obtained after step 1 is placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min under an argon atmosphere, pre-carbonized for 3 hours, cooled to room temperature, taken out, and ground;

[0076] Step 3: Plasma treatment: the material obtained after step 2 is placed in a plasma vapor deposition chamber, CH4 is introduced at a gas input flow rate of 15 mL / s, the plasma input power is 200 W, and the temperature is increased to 200°C at a rate of 5°C / min, and the temperature is kept for 20 min. After the heat preservation is completed, the sample is cooled to room temperature with the furnace to obtain a plasma-treated sample;

[0077] Step 4: High-temperature carbonization: the plasma-treated sample obtained after step 3 was placed in a tube furnace and heated to 1300 °C at 2 °C / min for 3 h. The sample was then cooled to room temperature and ground to obtain a bamboo powder pyrolysis hard carbon material.

[0078] Step 5: using the carbon material prepared above as an active material of a negative electrode material of a battery for preparing a sodium ion battery, the specific method is the same as that of Example 1;

[0079] Step 6: The material prepared above is used as the active material of the battery negative electrode material for measuring the gas production during the post-recycling process of the sodium ion battery. The specific method is the same as that in Example 1.

[0080] Example 5

[0081] A method for preparing a biomass hard carbon negative electrode material for a sodium ion battery comprises the following steps:

[0082] Step 1: Drying: 5 g of bamboo powder was placed in a forced air drying oven at 80 °C for 2 h to remove moisture;

[0083] Step 2: Pre-carbonization: the precursor obtained after step 1 is placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min under an argon atmosphere, pre-carbonized for 3 hours, cooled to room temperature, taken out, and ground;

[0084] Step 3: Plasma treatment: the material obtained after step 2 is placed in a plasma vapor deposition chamber, CH4 is introduced at a gas input flow rate of 10 mL / s, the plasma input power is 200 W, and the temperature is increased to 200°C at a rate of 5°C / min, and the temperature is kept for 25 min. After the heat preservation is completed, the sample is cooled to room temperature with the furnace to obtain a plasma-treated sample;

[0085] Step 4: High-temperature carbonization: the plasma-treated sample obtained after step 3 was placed in a tube furnace and heated to 1300 °C at 2 °C / min for 3 h. The sample was then cooled to room temperature and ground to obtain a bamboo powder pyrolysis hard carbon material.

[0086] Step 5: using the carbon material prepared above as an active material of a negative electrode material of a battery for preparing a sodium ion battery, the specific method is the same as that of Example 1;

[0087] Step 6: The material prepared above is used as the active material of the battery negative electrode material for measuring the gas production during the post-recycling process of the sodium ion battery. The specific method is the same as that in Example 1.

[0088] Example 6

[0089] A method for preparing a biomass hard carbon negative electrode material for a sodium ion battery comprises the following steps:

[0090] Step 1: Drying: 5 g of bamboo powder was placed in a forced air drying oven at 80 °C for 2 h to remove moisture;

[0091] Step 2: Pre-carbonization: the precursor obtained after step 1 is placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min under an argon atmosphere, pre-carbonized for 3 hours, cooled to room temperature, taken out, and ground;

[0092] Step 3: Plasma treatment, the material obtained after step 2 is placed in a plasma vapor deposition chamber, Ar flowing from toluene liquid is introduced at a gas input flow rate of 10 mL / s, and in the plasma gas phase, the plasma input power is 200 W, and the temperature is increased to 200 °C at 5 °C / min, and the temperature is kept for 20 min. After the insulation is completed, the sample is cooled to room temperature with the furnace to obtain a plasma-treated sample;

[0093] Step 4: high temperature carbonization. The plasma-treated sample obtained after step 3 is placed in a tube furnace and heated to 1300 °C at 2 °C / min. High temperature carbonization is performed for 3 h. The sample is cooled to room temperature and ground to obtain bamboo powder pyrolysis hard carbon material.

[0094] Step 5: The carbon material prepared above is used as the active material of the battery negative electrode material for the preparation of a sodium ion battery, and the specific method is the same as that of Example 1; the first cycle charge and discharge curve of the sodium ion battery is as follows: Figure 3 shown.

[0095] Step 6: The material prepared above is used as the active material of the battery negative electrode material for measuring the gas production during the post-recycling process of the sodium ion battery. The specific method is the same as that in Example 1.

[0096] Example 7

[0097] A method for preparing a biomass hard carbon negative electrode material for a sodium ion battery comprises the following steps:

[0098] Step 1: Drying: 5 g of bamboo powder was placed in a forced air drying oven at 80 °C for 2 h to remove moisture;

[0099] Step 2: Pre-carbonization: the precursor obtained after step 1 is placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min under an argon atmosphere, pre-carbonized for 3 hours, cooled to room temperature, taken out, and ground;

[0100] Step 3: Plasma treatment, the material obtained after step 2 is placed in a plasma vapor deposition chamber, Ar flowing from the cyclohexane liquid is introduced at a gas input flow rate of 10 mL / s, and in the plasma gas phase, the plasma input power is 200 W, and the temperature is increased to 200 °C at 5 °C / min, and the temperature is kept for 20 min. After the end of the heat preservation, the sample is cooled to room temperature with the furnace to obtain a plasma-treated sample;

[0101] Step 4: High-temperature carbonization: the plasma-treated sample obtained after step 3 was placed in a tube furnace and heated to 1300 °C at 2 °C / min for 3 h. The sample was then cooled to room temperature and ground to obtain a bamboo powder pyrolysis hard carbon material.

[0102] Step 5: using the carbon material prepared above as an active material of a negative electrode material of a battery for preparing a sodium ion battery, the specific method is the same as that of Example 1;

[0103] Step 6: The material prepared above is used as the active material of the battery negative electrode material for measuring the gas production during the post-recycling process of the sodium ion battery. The specific method is the same as that in Example 1.

[0104] Example 8

[0105] A method for preparing a biomass hard carbon negative electrode material for a sodium ion battery comprises the following steps:

[0106] Step 1: Drying: 5 g of peanut shell powder was placed in a forced air drying oven at 80 °C for 2 h to remove moisture;

[0107] Step 2: Pre-carbonization: the precursor obtained after step 1 is placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min under an argon atmosphere, pre-carbonized for 3 hours, cooled to room temperature, taken out, and ground;

[0108] Step 3: Plasma treatment: the material obtained after step 2 is placed in a plasma vapor deposition chamber, CH4 is introduced at a gas input flow rate of 10 mL / s, the plasma input power is 200 W, and the temperature is increased to 200°C at a rate of 5°C / min, and the temperature is kept for 20 min. After the heat preservation is completed, the sample is cooled to room temperature with the furnace to obtain a plasma-treated sample;

[0109] Step 4: high temperature carbonization. The plasma-treated sample obtained after step 3 is placed in a tube furnace and heated to 1300 °C at 2 °C / min. High temperature carbonization is performed for 3 h. The sample is cooled to room temperature and ground to obtain a peanut shell powder pyrolysis hard carbon material.

[0110] Step 5: The carbon material prepared above is used as the active material of the battery negative electrode material for the preparation of a sodium ion battery, and the specific method is the same as that of Example 1; the first cycle charge and discharge curve of the sodium ion battery is as follows: Figure 4 shown.

[0111] Step 6: The material prepared above is used as the active material of the battery negative electrode material for measuring the gas production during the post-recycling process of the sodium ion battery. The specific method is the same as that in Example 1.

[0112] Comparative Example 1

[0113] A method for preparing a biomass-based hard carbon negative electrode material for a sodium ion battery, the steps comprising:

[0114] Step 1, drying: 5 g of bamboo powder was placed in a forced air drying oven at a drying temperature of 80 °C for 2 h to remove moisture;

[0115] Step 2, carbonization: the bamboo powder obtained after step 1 is placed in a tube furnace, heated to 400°C at a heating rate of 2°C / min under an argon atmosphere, pre-carbonized for 3 hours, cooled to room temperature, then heated to 1300°C at 2°C / min, high-temperature carbonized for 3 hours, cooled to room temperature, ground and crushed to obtain a bamboo powder pyrolysis hard carbon electrode material;

[0116] Step 3: Assemble the biomass-based hard carbon negative electrode material prepared above into a sodium ion battery.

[0117] According to the mass ratio of 92%:3%:1.5%:3.5%, 184 mg of bamboo powder pyrolysis hard carbon electrode material powder, 6 mg of conductive carbon black, 6 mg of 2% (w / w) carboxymethyl cellulose solution, and 17.5 mg of 40% (w / w) styrene-butadiene rubber were weighed, and an appropriate amount of deionized water was added dropwise. The mixture was stirred for 20 min until it became a uniform slurry. A 100 μm scraper was used to evenly coat the slurry on the surface of the copper (Cu) foil, and the slurry was dried in a forced air drying oven at 105 °C for 2 h. The Cu foil with active material was cut into disc-shaped negative electrode sheets, which were then transferred to a glove box for standby use.

[0118] The assembly of the simulated battery was carried out in a MIKROUNA glove box filled with Ar atmosphere, using the prepared carbon material electrode as the negative electrode, commercial electrolyte 1.0 mol / L NaPF6 / EC:DMC (1:1) (V:V) as the electrolyte, and Na metal sheet as the counter electrode to assemble a 2016 button cell. The first cycle charge and discharge curve of the sodium ion battery is shown in Figure 2. Figure 5 shown.

[0119] Step 4: Assemble the biomass-based hard carbon negative electrode material prepared above into a sodium ion battery and measure its gas production during the cycle.

[0120] The measurement of battery gas production requires assembly into a soft-pack battery first. Commercial nickel-iron-manganese layered oxide is used for the positive electrode, and the prepared hard carbon is used for the negative electrode. The negative electrode is slurried, coated, dried, die-cut, stacked, injected, and soft-pack packaged in a mass ratio of 92%:3%:1.5%:3.5% to assemble into a single soft-pack battery with a capacity of 1 Ah. The volume measurement of soft-pack batteries is mainly based on the Archimedean principle. The soft-pack battery is hung on a universal testing machine, the reading is recorded, and then the battery is slowly and completely immersed in non-conductive vacuum pump oil (density 0.8595 cm -3 ), record the reading of the tensile instrument again after the instrument stabilizes, which is the volume of the soft-pack battery, and the volume difference before and after the cycle is the gas production.

[0121] Table 1 Performance parameters of the half-cells assembled in Comparative Example 1 and Examples 1 to 8

[0122]

[0123] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a sodium ion battery biomass hard carbon negative electrode material, characterized in that: The steps include: S1: Pretreatment: drying the biomass raw material; S2: Pre-carbonization: pre-carbonizing the pretreated biomass; S3: plasma treatment: subjecting the pre-carbonized biomass to plasma coating treatment; S4: high temperature carbonization: high temperature carbonization of the biomass after plasma treatment to obtain a biomass hard carbon negative electrode material for a sodium ion battery; Among them, the pre-carbonization temperature is 400 °C and the pre-carbonization time is 3 h; The plasma treatment temperature was 200 °C, the input power was 200 W, the gas input was 10 mL / s, and the holding time was 20 min; The high temperature carbonization temperature is 1300 °C and the high temperature carbonization time is 3 h; Hydrocarbons are introduced during plasma treatment; The biomass raw material is bamboo powder; and the hydrocarbon is methane.

2. The sodium ion battery biomass hard carbon negative electrode material obtained by the preparation method according to claim 1.

3. A sodium ion battery, characterized in that: Including the sodium ion battery biomass hard carbon negative electrode material as described in claim 2.